Deteksi dini kanker serviks dengan metode pulasan papsmear pada wanita aktif secara seksual di Kecamatan Gandus - Dewi, Citra; Kartika, Ika; Fauziah, Nyiayu; Ulfa, Maria; Desmaradd, Soraya Sagita; Ramkita, Nora; Sari, Pratia Mega; Suzena, Yayuk; Seda, Andi; Sandria, Sandria; Septa, Fadly; Libel, Eduwardo; Noprianti, Vivin; Fitri, Eka (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2024)
Cervical cancer is one of the most common cancers in women around the world after breast cancer. Persistent Human Papillomavirus (HPV) infections, especially types 16 and 18, are known to be the main cause of cervical cancer. Currently, preventive programs such as papsmear reviews are prioritized to reduce the incidence and mortality of cervical cancer. This community service activity aims to screen cervical cancer in sexually active women and increase public awareness about the importance of papsmear screening. This activity was located at Gandus Hospital, South Sumatra, involving as many as 31 participants, with the results of the examination obtained normal in 10 respondents (32.2%), atrophic smear in 2 respondents (6.4%), chronic cervicitis in 18 respondents (58.1%) and LGSIL in 1 respondent (3.2%). The characteristics of the respondents in this activity include, women under 40 years old with a general educational background of college or equivalent. The age of marriage or the age of the respondent's first sexual activity and the age of giving birth to the first child at the age of 16-25 years. The number of the most respondent children was less than or equal to 2 children. The use of contraceptives used by the most respondents was spiral contraception. The results of the screening examination found 1 respondent with LGSIL, so proper medical treatment was needed and the precancerous lesion did not continue to become cervical cancer.